The efficiency assessment of Ni(40)Ti(50)Cu(x)Fe(10-x) shape memory alloy produced by combustion synthesis through thermal analysis - Keskin, Berk; Derin, Bora (My University, 2024)
In this investigation, Ni(40)Ti(50)Cu(x)Fe(10−x) (x = 2.5, 5, 7.5) alloys were synthesized through the self-propagating high-temperature synthesis (SHS) process, employing preheating temperatures of 240 and 450 °C. To optimize thermal analysis, samples were drawn from the middle and upper sections of specimens exhibiting superior propagation results at a preheating temperature of 450 °C. Omitting additional heat treatment ensured a precise result interpretation. While the Ti50Ni40Fe2.5Cu7.5 sample displayed minimal variations in martensite and austenite transformation temperatures, others exhibited diverse transformation profiles. Apart from the B19' martensitic phase, distinct B19 martensitic phases were identified in Ti50Ni40Fe5Cu5 and Ti50Ni40Fe2.5Cu7.5 alloys, each showcasing unique transformation temperatures and full-width at half-maximum (FWHM) values. The inquiry unveiled that an increased Fe content prompted the segregation of Fex(Ni)Ti-based intermetallic phases from Cu-based phases, with this effect intensifying in alloys featuring higher Fe atomic ratios. This influence significantly impacted transformation temperature outcomes, overshadowing the inherent impact of the synthesis method.
Keywords: Factsage; NiTiCuFe; Shape–Memory Alloys; SHS; Thermal Analysis